Penguatan Pendidikan Karakter dalam Pendidikan Islam: Tantangan dan Strategi di Era Disrupsi - Rahmadani Akbar; Rahmad Alkhadafi (Penerbit Hellow Pustaka, 2025)
Character education plays an important role in shaping a person's character, especially in the era of disruption marked by the development of technology and globalization. In this context, Islamic education is expected to overcome moral challenges through strengthening character education. This study aims to understand the implementation of strengthening character education in Islamic education, identify the challenges faced, and propose appropriate strategies. The method used in this study is library research, which critically analyzes various related literature. The results of this study indicate that character education requires a holistic approach through the integration of Islamic values in the curriculum, the use of technology as a learning medium, the development of teacher competencies, and tri-center collaboration between families, schools, and communities. The challenges faced include the influence of technology that can hurt student morals, changes in socio-cultural values , and the readiness of teachers who are required to integrate digital media in Islamic education. The proposed strategy emphasizes cross-sector collaboration to create continuity in character education. By implementing this approach, Islamic education can produce a generation that is not only intellectually intelligent but also has a strong character, so that it can face the challenges of the digital era with strong Islamic moral values.